2005
DOI: 10.1080/14660820510028412a
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of motor neuron disease in Hong Kong

Abstract: Worldwide, the incidence of motor neuron disease (MND) has been increasing steadily over recent decades. We reported a follow-up epidemiology study of MND in this locality. We identified the subjects from the computer database of the government hospital system between 1 January 1997 and 31 January 2002 by searching the ICD code starting from 335.xx. Every retrieved case or their records were reviewed and validated by neurologist(s) of the responsible regional hospitals which the patients attended. One hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 0 publications
8
34
2
2
Order By: Relevance
“…The incidence of ALS was 0.77 cases per 100,000 person-years (95% CI 0.71–0.83). The incidence rate in the present study is similar to the rates reported by several recent studies across East Asia [5], Hong Kong [9], Taiwan [10] and Russia [11] (Table 2). On the other hand, studies across Europe and the United States tend to report a higher incidence.…”
Section: Discussionsupporting
confidence: 81%
“…The incidence of ALS was 0.77 cases per 100,000 person-years (95% CI 0.71–0.83). The incidence rate in the present study is similar to the rates reported by several recent studies across East Asia [5], Hong Kong [9], Taiwan [10] and Russia [11] (Table 2). On the other hand, studies across Europe and the United States tend to report a higher incidence.…”
Section: Discussionsupporting
confidence: 81%
“…The estimated prevalence in our study was close to the prevalence reported for the city of Jefferson in the USA (3.9/100,000) 13 , in Modena, Italy (4.02/100,000) 8 , in the Republic of Ireland (4.7/100,000) 14 , in Ontario, Canada (4.9/100,000) 15 and in southeast England (4.91/100,000) 16 . On the other hand, our estimated prevalence is higher than the prevalence of ALS reported in Isfahan, Iran (1.57/100,000) 17 , in Uruguay (1.9/100,000) 11 and in Hong Kong, China (3.04/100,000) 18 , and lower than the prevalence of ALS reported in Italy (7.89/100,000) 19 and in the Netherlands (10.32/100,000) 9 . In our analysis of the results by gender, we found a hi gher prevalence of ALS for men (5.2/100,000) compared to wo men (4.8/100,000).…”
Section: Discussioncontrasting
confidence: 50%
“…This limitation was not only inevitable in this study, which depended on the NHI research database, but also reflected a real-world phenomenon. Similar limitations also existed in the epidemiological study of MND by Fong et al [12] in Hong Kong, which used ICD-9 diagnostic criteria.…”
Section: Sexmentioning
confidence: 99%
“…The average incidence of MND was 0.31 per 100,000/year in Hong Kong Chinese between 1989 and 1992 [13] and 160 increased to 0.60 per 100,000/year during 1997-2002 [12] . The crude incidence rate of sporadic MND from 1980 to 1989 was 0.69 per 100,000/year on Japan's Hokkaido island [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation